A Multifunctional Magnetic Material under Pressure. Issue 26 (7th May 2014) - Rodríguez‐Velamazán, J. Alberto; Fabelo, Oscar; Beavers, Christine M.; Natividad, Eva; Evangelisti, Marco; Roubeau, Olivier
Abstract FeII(Metz)6](FeIIIBr4)2 (Metz=1‐methyltetrazole) is one of the rare systems combining spin‐crossover and long‐range magnetic ordering. A joint neutron and X‐ray diffraction and magnetometry study allows determining its collinear antiferromagnetic structure, and shows an increase of the Néel temperature from 2.4 K at ambient pressure, to 3.9 K at 0.95 GPa. Applied pressure also enables a full high‐spin to low‐spin switch at ambient temperature.